Historical Studies: The Social Life Of Muslim Minorities In The United States - Azizah, Faras Puji; Aprilia, Mona (Tanjak: Sejarah dan Peradaban Islam, 2024)
This article describes the history of Islamic civilization in the Muslim minority country of America. The United States is secular but provides opportunities for every religion to grow and develop. The development of Islam in America cannot be separated from the scholars there. The method used in this paper is the Library research method (literature study). The results of this study noted that Islam is very developed in America compared to other religions when many Americans embrace Islam. Several Islamic financial and banking institutions were established in America Finance House Riba in California, which offers home financing based on Sharia principles. In addition, the emergence of Islamic economics and finance in this country was not as smooth as in other countries. Muslim minorities have established large organizations to help each other, such as ISNA, CAIR, and Islamic Relief USA.